Ensino de sociologia, escola e juventudes: proposta de material didático - Ferreira, Felipe Barreira (2020)
This work results in the production of didactic material that emphasizes the analytical and empirical role that the school can acquire for teaching school sociology, and can serve as didactic support for teachers and students of high school sociology interested in discussing the relevance of school education and from school, both for society as a whole, as well as for individuals who live daily in this educational institution that occupies or has occupied a relevant time in the lives of practically all of us, especially young students. To justify such an undertaking, it was investigated what place education and school occupy in the sociology textbooks for high school selected by the Programa Nacional do Livro Didático (PNLD) in its three editions (2012, 2015, 2018), concluding that the sociological reflection on the school, rich and abundant in the production of Social Sciences in general, is practically absent from the sociology textbooks chosen by the PNLD, as is evident here through the analysis of all 13 school discipline textbooks. In an attempt to minimize the marginalization of the school as an object of teaching school sociology in the textbooks of the discipline, a didactic material was produced that addresses essential aspects about school education and the school, highlighting different interpretations of the school as a social institution and as a place of interactions and groupings, which reveal a rich opportunity not only for reflection on the sociological character of the school, but also for the teaching of sociology itself by focusing on the social phenomena that can be observed on the floor of the secondary school and in the youths who experience it daily.